1992
DOI: 10.1007/bf00224001
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphism evaluation of six peanut species within the Avachis section

Abstract: Restriction fragment length polymorphisms (RFLP) were assessed among accessions within six peanut species of the Arachis section: tetraploid cultivated species, A. hypogaea; tetraploid wild species, A. monticola; and four diploid wild species, A. batizocoi,A. cardenasii, A. duranensis and A. glandulifera. While the two tetraploid species did not show polymorphism with 16 PstI-generated random genomic probes, two of seven seed cDNA probes detected polymorphisms. The RFLP variation detected by two seed cDNA prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 21 publications
2
50
0
3
Order By: Relevance
“…The phylogenetic relationships in the genus Arachis have also been studied using different molecular markers, such as seed protein profiles (Singh et al, 1991;Singh et al, 1994), isoenzymes (Stalker et al, 1994;Maass and Ocampo, 1995;Galgaro et al, 1997), RAPDs (Halward et al, , 1992Gimenes et al, 2000), and RFLPs Paik-Ro et al, 1992;Stalker et al, 1995;Kochert et al, 1996, Galgaro et al, 1998. All those markers have generated information that has been very useful for solving taxonomic and phylogenetic questions in this genus.…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetic relationships in the genus Arachis have also been studied using different molecular markers, such as seed protein profiles (Singh et al, 1991;Singh et al, 1994), isoenzymes (Stalker et al, 1994;Maass and Ocampo, 1995;Galgaro et al, 1997), RAPDs (Halward et al, , 1992Gimenes et al, 2000), and RFLPs Paik-Ro et al, 1992;Stalker et al, 1995;Kochert et al, 1996, Galgaro et al, 1998. All those markers have generated information that has been very useful for solving taxonomic and phylogenetic questions in this genus.…”
Section: Introductionmentioning
confidence: 99%
“…This unique association supports the view that the subsp. hypogaea is much closer to wild allotetraploid (Paik-Ro et al 1992;Singh et al 1993;He and Prakash 2001), and that AhMITE1 transposition at an FST1-linked site could have played a key role in the origin of subsp. fastigiata.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of species outside section Arachis have been infrequent. Stalker (1985) reported that the two diploid section Erectoides species A. rigonii 3 A. paraguariensis hybrids had many univalents and Krapovickas and Gregory (1994) (Lu and Pickersgill, 1993;Stalker et al, 1994), seed storage proteins (Singh et al, 1991;Bianchi-Hall et al, 1993;Liang et al, 2006), Restriction Fragment Length Polymorphisms (RFLPs) Paik-Ro et al, 1992), Amplified Fragment Length Polymorphisms (AFLPs) (Milla-Lewis et al, 2005b); Simple Sequence Repeats (SSRs) (Hopkins et al, 1999;He et al, 2005;Hong et al, 2010;Guo et al, 2012;Nagy et al, 2012). Randomly Amplified Polymorphic DNA (RAPDS) (Halward et al, 1992;Lanham et al, 1992;Hilu and Stalker, 1995), and in situ hybridization (Raina and Mukai, 1999;Seijo et al, 2004).…”
Section: Cytology and Evolution Of Arachismentioning
confidence: 99%
“…The nature and the possibility of using molecular markers have been evolving as have all aspects of the agronomical sciences. The first molecular marker studies used for peanut were based on isozymes and proteins (Grieshammer and Wynne, 1990;Krishna and Mitra, 1988;Lu and Pickersgill, 1993), followed by Restriction Fragment Length Polymorphism -RFLPs Kochert et al, 1996;Paik-Ro et al, 1992), Random Amplified Polymorphic DNA -RAPDs Halward et al, 1992;Hilu and Stalker, 1995;Subramanian et al, 2000;Dwivedi et al, 2001;Raina et al, 2001) and Amplified Fragment Length Polymorphism -AFLPs (He and Prakash, 1997;Gimenes et al, 2000;Gimenes et al, 2002;Herselman, 2003;Milla et al, 2005aMilla et al, , 2005bTallury et al, 2005).…”
Section: Introgressing Genes From Arachis Species To a Hypogaeamentioning
confidence: 99%